Identification of Psychological Development Challenges Among Adolescents in Madrasah Aliyah and Their Implications for Student Guidance Patterns - Fradilla, Riska; Azzahra, Rahmi Latifa; Rahman, Rahman (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to identify the psychological development challenges faced by adolescents in Madrasah Aliyah, the contributing factors, students’ forms of response, the guidance patterns implemented, their implications for the guidance process, and relevant guidance strategies. This research employs a descriptive qualitative approach with primary and secondary data obtained through a literature review. Data were collected through documentation studies and analyzed using content analysis. The findings indicate that adolescents in Madrasah Aliyah encounter various psychological challenges such as identity conflict, academic pressure, emotional instability, and the influence of digital environments. Students’ responses include both adaptive and maladaptive coping strategies. The guidance provided by the madrasah tends to focus on moral and academic aspects, and therefore has not fully addressed the emotional needs of adolescents. Consequently, an integrative guidance model is needed, encompassing emotional, social, and religious reinforcement, along with collaboration among teachers, counselors, and parents.